Application of Fractional Wave Packet Transform for Robust Watermarking of Mammograms - Pushpa Mala Siddaraju; Devappa Jayadevappa; Kaliyamoorthy Ezhilarasan (International Journal of Telemedicine and Applications)
Exchanging of medical data requires efficient authentication and protection of medical data that can be illegally modified. Watermarking plays an important role in protecting, sharing, and securing medical data. In this work, a robust nonblind medical image watermarking scheme is proposed. The process involves two steps: the embedding and the extraction phase. During the embedding phase, l-level FRWPT is performed on the host image and the watermark is embedded into the modified reference image. In the second phase, inverse FRWPT is performed on the watermarked image to extract the watermark from the watermarked image. The proposed scheme is tested on mammograms images and is subjected to common attacks like Gaussian filtering, median filtering, compression, sharpening, and contrast adjustments. Experimental results show that the proposed scheme is robust.